Evaluation of the knowledge, attitude and practices regarding oral health of the schoolteachers in Mangalore city - Nishi Gupta; N Vanishree; Ashwini Rao; V Chaithra; Deepa Bullappa; R V Bharathi (Wolters Kluwer Medknow Publications, 2015)
Introduction: School teachers can play a significant role in school dental health education as they can bring about changes in the attitudes and behavior of the children at a very young age, which is long lasting. Objectives: To assess the knowledge, attitude and practice of the primary and middle school teachers. Materials and Methods: A cross-sectional survey was carried out on 241 primary and middle school teachers from 17 selected schools in Mangalore city and was given the questionnaires in English as well as the local language Kannada. There were 18 questions regarding knowledge about dental diseases such as dental caries, periodontal disease, oral hygiene practices, tobacco chewing habits and smoking habits. Results: About 241 (100%) had heard about tooth decay and 228 (94.6%) had heard of gum disease. An inverse relationship between the frequency of changing the brush and awareness about dental caries was observed people with a chewing habit and smoking habit had a low level of knowledge and awareness about the dental caries and periodontal disease. Conclusions: Since the information was gained more from dentists and televisions, more dental health programs should be encouraged in televisions and dentists should play a vital role in enlightening people about oral health.